Preparation and characterization of aluminum substitute yttrium iron garnet nanoparticles by sol–gel technique - Al-Habashi, Ramadan Masoud; Yahya, Noorhana; Shafie, Mohd Shamsul Ezzad; Ismail, Ismayadi; Bawa Waje, Samaila; Mohd Saad, Mohd Hashim (Universiti Putra Malaysia Press, 2005)
This paper presents preparation and characterization of aluminum substituted–iron garnet (Al-YIG) nanocrystalline powder. The samples were synthesized using sol–gel technique. The gel was prepared from Al(NO3)3.9H2O, Y(NO3)3.6H2O and Fe(NO3)3.9H2O. They were mixed and dissolved together in C6H8O7.H2O for a month to formation the gel form by magnetic stirrer equipment at 350 rpm. The sample was then dried at 110⁰C in an oven for a day to remove the unneeded water before it was calcined and crushed to obtain a fine particles powder. The calcined powder at 700⁰C, 750⁰C, 800⁰C, 850oC and 900⁰C was characterized by X-ray diffraction analysis (XRD) to confirm the garnet and the best garnet phase. Finally, Scanning Electron Microscopy (SEM) was used to study the morphology of sample. The results showed that, the best garnet phase appeared when the sintering temperature was 800⁰C and (Al-YIG) nanocrystals with sizes ranging from 50 to 100 nm were formed.